Two neuronal peptides encoded from a single transcript regulate mitochondrial complex III in Drosophila - Justin A Bosch; Berrak Ugur; Israel Pichardo-Casas; Jordan Rabasco; Felipe Escobedo; Zhongyuan Zuo; Ben Brown; Susan Celniker; David A Sinclair; Hugo J Bellen; Norbert Perrimon (eLife, 2022)
Naturally produced peptides (<100 amino acids) are important regulators of physiology, development, and metabolism. Recent studies have predicted that thousands of peptides may be translated from transcripts containing small open-reading frames (smORFs). Here, we describe two peptides in Drosophila encoded by conserved smORFs, Sloth1 and Sloth2. These peptides are translated from the same bicistronic transcript and share sequence similarities, suggesting that they encode paralogs. Yet, Sloth1 and Sloth2 are not functionally redundant, and loss of either peptide causes animal lethality, reduced neuronal function, impaired mitochondrial function, and neurodegeneration. We provide evidence that Sloth1/2 are highly expressed in neurons, imported to mitochondria, and regulate mitochondrial complex III assembly. These results suggest that phenotypic analysis of smORF genes in Drosophila can provide a wealth of information on the biological functions of this poorly characterized class of genes.